2011
DOI: 10.1501/vetfak_0000002457
|View full text |Cite
|
Sign up to set email alerts
|

Akkaraman ırkı koyunlarda transrektal ve transabdominal muayene tekniği kullanılarak embriyonik ve fötal yaşın belirlenmesi

Abstract: Determination of embryonic and fetal age by transrectal and transabdominal ultrasonographic examination in Akkaraman ewesSummary: This study was performed in order to determine gestational age in ewes by fetometry. For this purpose, a total of 10 Akkaraman ewes were examined by using ultrasonography supported by a linear array transducer. In order to find an equation to calculate the gestational age (GA) by using fetometric method, the parameters of diameter of embryonic vesicle (EVD), crown-rump length (CRL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Upon determining that the uterus hung from the intrapelvic area to the abdominal cavity on the 32nd day of pregnancy in Akkaraman sheep, Küplülü et al (2002) suggested the use of the transabdominal technique for the diagnosis of pregnancy by ultrasound examination, as of day 32. The application of transabdominal ultrasonography in the sitting position has been reported to produce better results than the standing position for early pregnancy diagnosis (Gürler and Kaymaz, 2011). However, maintaining animals in a sitting position is time-consuming and laborsome.…”
Section: Resultsmentioning
confidence: 99%
“…Upon determining that the uterus hung from the intrapelvic area to the abdominal cavity on the 32nd day of pregnancy in Akkaraman sheep, Küplülü et al (2002) suggested the use of the transabdominal technique for the diagnosis of pregnancy by ultrasound examination, as of day 32. The application of transabdominal ultrasonography in the sitting position has been reported to produce better results than the standing position for early pregnancy diagnosis (Gürler and Kaymaz, 2011). However, maintaining animals in a sitting position is time-consuming and laborsome.…”
Section: Resultsmentioning
confidence: 99%